Free flap outcome of salvage surgery compared to primary surgery for head and neck defects: A propensity score analysis. (November 2016) - Baek, Chung-Hwan; Park, Woori; Choi, Nayeon; Gu, Seonhye; Sohn, Insuk; Chung, Man Ki
Highlights: Free flap outcomes for head and neck defects between primary and salvage surgery. Propensity score analysis was used to retrieve balanced subpopulation. Complications and flap success rate was not different between two groups. Free flap is reliable in previously irradiated/operated surgical field. Abstract: Objectives: To compare free flap outcomes for head and neck defects between primary surgery and salvage surgery and identify factors affecting the outcomes in the two settings. Methods: A total of 225 patients (primary group, n = 56; salvage group, n = 169) were retrospectively identified. The salvage group was previously treated with radiotherapy, chemoradiation, surgery, or any combination of these treatments. Clinical data were retrieved and analyzed between the two groups to compare the incidence and contributing factors of flap-related complications and flap failure. A propensity score analysis with matching T stage, defect, and flap types was also performed for unbiased comparisons. Results: Flap-related complication rate was 22.2% in all patients. The salvage group showed higher rates of wound dehiscence than the primary group (3.6% in primary vs. 13.0% in salvage; p  = 0.04). Flap failures occurred in 10 patients (4.4%), including 3 (5.4%) in the primary group and 7 (4.1%) in the salvage group ( p  = 0.71). Multivariate analysis showed no critical factor that influenced the occurrence of flap-related complications or flap failure, including surgery type (primary or salvage). In propensity score analysis, incidences and types of flap-related complications and flap failure were not statistically different between the two groups (primary and salvage). Conclusions: Free flap reconstruction is a safe and reliable method to restore the ablative defects in previously irradiated or operated head and neck defects.